Exploring the Characteristics and Extent of Travel Influencers’ Impact on Generation Z Tourist Decisions - Codruța Băltescu; Elena-Nicoleta Untaru (My University, 2024)
The social media phenomenon revolutionized the way people communicate and share information in all age groups. In the context of global expansion and its undeniable popularity, social media platforms have favored the emergence of a new concept, the social media influencer (SMI). SMIs are online celebrities, followed and copied by a large number of users. The paper’s goal is to investigate the capacity of travel SMIs to influence the tourist decisions of Generation Z members. Aiming to obtain insight results, an exploratory study was conducted using the qualitative focus group research method. The respondents are members of Generation Z, users of social media platforms for travel planning. The main results highlight the characteristics of travel SMIs’ activities and influences, as well as the advantages and disadvantages of following their recommendations in the travel planning process. Also, this study highlights the reduced influence of Romanian travel SMIs on Generation Z tourists, despite the fact that they are primary information consumers on this communication channel. The results could contribute to establishing general benchmarks of a future professional career for Generation Z members as travel SMIs, an important sustainable option for communication in tourism.
Keywords: Generation Z; social media platforms; travel SMIs; tourist decisions